Identidad segregada: construcción de la imagen de la mujer en Venezuela y América Latina desde la colonialidad (Dissertare Revista de Investigación en Ciencias Sociales, 2018)
In Venezuela, women's studies emerged since the seventies of the twentieth century. Those who referred to the female condition did so from the perspective of the latter as a historical condition of oppression and alienation developed since colonial times (Comesaña-Santalices, 1998, Vargas, 2010). The historiographic review presented in this article constitutes a phase of the Doctoral Thesis "Oral Accounts of Women from Humocaro Alto in Lara State: Language, Culture and Identity" (research in development). This allowed  us to clarify what historical and philosophical studies propose about what it means to be a woman in Venezuela (within the framework of Latin America). It also allowed to contrast it later, ethnohistorically with empirical ethnographic and linguistic data in a later stage of research. The objective of this methodological moment was to analyze the feminine identity as an ontological project for the construction of the image of women in Venezuela and Latin America, within the framework of colonial logic. The hermeneusis was made under the modality of documentary research using the bibliographic observation and the signing as data collection techniques. It was used the critical analysis of the sources for the treatment of the information . Results are teleologically philosophical,  despite of the inclusion of historiographic precision.  They allowed us to understand, from the historical data, how feminine identity is a segregated femininity constructed as a wild femininity buried by chastity (as a cannibal trope), which emerged as an ontological construction project that devours the difference and otherness of the Other.
Keywords: identidad; feminidad-castidad; colonialidad; identidad femenina en Venezuela